Radiation Segmentectomy - Prachanronarong, Kristina; Kim, Edward (Seminars in Interventional Radiology, 2021)
Radiation segmentectomy is an yttrium-90 transarterial radioembolization treatment where a high radiation dose is administered to a small volume of liver to achieve a high tumoricidal dose to a target with anatomic surgical precision while sparing surrounding parenchyma. This therapeutic modality is often used to treat hepatocellular carcinoma, and recent studies have demonstrated that radiation segmentectomy is an effective treatment as a neoadjuvant to transplant, resection, or as a standalone treatment. This article provides a review of radiation segmentectomy, indications for treatment, recent outcome data, and guidelines for postprocedural management.
Keywords: radioembolization; radiation segmentectomy; hepatocellular carcinoma; interventional radiology